New occurrence of reed bed decline in southern Europe: do permanent flooding and chemical parameters play a role? - Gigante, Daniela; Angiolini, Claudia; Landucci, Flavia; Maneli, Fabio; Nisi, Barbara; Vaselli, Orlando; Venanzoni, Roberto; Lastrucci, Lorenzo (Comptes rendus biologies, 2014)
Based on the experimental design proposed in similar studies, macromorphological and ecological traits of common reed beds were analysed at Lake Chiusi (Central Italy), together with selected chemical parameters in sediments and interstitial waters and aerial images of the site, in order to investigate reed decline and search for possible correlations among data. Typical symptoms of the reed dieback syndrome were detected, thus enlarging the occurrence of this phenomenon in southern Europe. Permanently dry, permanently flooded and partially flooded stands show different levels of decline, with the permanent flooding always co-occurring with reed dieback. Only few of the considered chemical parameters seem to play a role in reed decline (nitrates, rubidium, nickel, barium, manganese), although no clear pattern was identified. Data suggest that the co-occurrence of some chemicals with stressing conditions might affect the growth even of an efficient metal accumulator, as reed is generally considered.
Keywords: Metals; fyziologie rostlin; lipnicovité; Ecosystem; životní prostředí; Environment; Itálie; Mediterranean basin; Phragmites australis; kovy; Lakes; látky znečišťující životní prostředí; jezera; Dieback; Environmental Pollutants; biodiverzita; Plant Physiological Phenomena; Poaceae; Food; Italy; potraviny; Reed retreat; ekosystém; Biodiversity